Tafa-2 plays an essential role in neuronal survival and neurobiological function in mice. (22nd August 2018) - Wang, Xiyi; Shen, Chunling; Chen, Xuejiao; Wang, Jinjin; Cui, Xiaofang; Wang, Yicheng; Zhang, Hongxin; Tang, Lingyun; Lu, Shunyuan; Fei, Jian; Wang, Zhugang
Abstract: Tafa is a family of small secreted proteins with conserved cysteine residues and restricted expression in the brain. It is composed of five highly homologous genes referred to as Tafa-1 to -5. Among them, Tafa-2 is identified as one of the potential genes responsible for intellectual deficiency in a patient with mild mental retardation. To investigate the biological function of Tafa-2 in vivo, Tafa-2 knockout mice were generated. The mutant mice grew and developed normally but exhibited impairments in spatial learning and memory in Morris water maze test and impairments in short- and long-term memory in novel object recognition test, accompanied with increased level of anxiety-like behaviors in open-field test and elevated plus maze test, and decreased level of depression-like behaviors in forced-swim test and tail-suspension test. Further examinations revealed that Tafa-2 deficiency causes severe neuronal reduction and increased apoptosis in the brain of Tafa-2 −/− mice via downregulation of PI3K/Akt and MAPK/Erk pathways. Conformably, the expression levels of CREB target genes including BDNF, c-fos and NF1, and CBP were found to be reduced in the brain of Tafa-2 −/− mice. Taken together, our data indicate that Tafa-2 may function as a neurotrophic factor essential for neuronal survival and neurobiological functions.